Association of ABO Blood Group and Body Mass Index: A Cross-Sectional Study from a Ghanaian Population. (27th March 2018) - Smith, Samuel; Okai, Isaac; Abaidoo, Chrissie Stansie; Acheampong, Emmanuel
Abstract : ABO blood group and body mass index (BMI) have individually been appraised as risk factors for certain diseases. From statistical perspective, it may be important to examine the relationship between the ABO blood antigen and BMI. This cross-sectional study involved 412 participants aged 18 to 46 at the Kwame Nkrumah University of Science and Technology (KNUST), Kumasi. Weight and height of participants were measured for BMI calculation; blood group determination was done using antisera. Blood group O was the most prevalent (51.2%), while Rhesus-positive individuals constituted 90.3%. 6.3% of the participants were obese, while 18.7% were overweight. There was significant (p = 0.006 ) higher prevalence of obesity in females (10.3%) than in males (3.4%). The study did not observe any significant difference by association of ABO blood group with gender (p = 0.973 ), BMI (p = 0.307 ), or Rhesus status (p = 0.723 ). Regarding gender (p = 0.400 ) and BMI (p = 0.197 ), no statistically significant difference was observed between Rhesus blood groups. The prevalence of overweight, obesity, blood type O, and rhesus positive observed among students in this study is largely similar to what has been reported in published studies in Ghana and from other countries. Overweight and obesity were not associated with ABO blood groups or Rhesus in this study.